DOMINGO MORATALLA, T. y FEITO GRANDE, L. (2020): Bioética narrativa aplicada. Madrid: Guillermo Escolar. - Redondo García, Antonio (Daimon Revista Internacional de Filosofia, 2023)
Reseña de DOMINGO MORATALLA, T. y FEITO GRANDE, L. (2020): Bioética narrativa aplicada. Madrid: Guillermo Escolar.